Hubungan antara Faktor Risiko Perdarahan dengan Kejadian Perdarahan Postpartum di RSUD Dr. Moewardi Surakarta Tahun 2012 - Larissa Amanda; Rustam Sunaryo; . Widardo (Nexus Kedokteran Klinik, 2014)
Background: Maternal mortality rate in Indonesia is relatively high compared to the other Asian countries. Postpartum hemorrhage is one of the major cause of maternal mortality. The increase in risk factors for hemorrhage in pregnancy and labor is known to contribute to the increase in cases of postpartum hemorrhage. The objective of this research was to know the correlation between risk factors for hemorrhage and occurrence of postpartum hemorrhage in Dr. Moewardi Hospital Surakarta in 2012. Methods: This research used descriptive analytical study by the case control approach. Case group was patients with postpartum hemorrhage in Dr. Moewardi Hospital Surakarta in 2012. Sample of the case group was taken by purposive sampling. Control group was postpartum patients in Dr. Moewardi Hospital Surakarta in 2012 who didnt experience of postpartum hemorrhage. Sample of the control group was randomly selected by simple random sampling from 45 patients who had spontaneus labor and 45 patients who had sectio caesarean which met the criteria of purposive sampling. This research was conducted by collecting data from 55 medical records of patients in case and control groups. The collected data were analyzed with Chi Square and logistic regression formulas. Results: The result of statistical analysis revealed significant diferrences between case and control groups for methods of labour with p values = 0,001 and r = 0,405. The results of statistical analysis for age, parity, anemia, birthweight and severe preeclampsia revealed no significant differences between case and control groups with each p values = 0,566, 0,423, 0,401 and 0,161. There were no eclampsia and polihidramnios patient in case and control groups. Conclusions: The results of this research revealed that there were a correlation between spontaneous labor with episiotomy, elective caesarean section, emergency caesarean section, assisted vaginal delivery with episiotomy and occurence of postpartum hemorrhage in Dr. Moewardi Hospital in 2012. Keywords: postpartum hemorrhage, risk factors for hemorrhage.